A review on the effectiveness of different cooling method in improving mechanical properties and mitigating heat-induced distortion of 3mm thick SS316L plate - GTAW single-pass buttwelds - Ahmad Zabidi Md Taib; Mohd Suffian Misaran@Misran; Abdullah Mohd Tahir (e-VIBS, Faculty of Science and Natural Resources, 2024)
The cooling method in welding has evolved from a post-weld heat treatment (PWHT) process to in-process cooling or continuous cooling during the welding procedure. The main reasons for this, in general, are to increase the cooling rate of the material to avoid the widespread area of heat input onto the base metal, which will lessen the wide heataffected zone (HAZ) and prevent HAZ softening phenomena. These chain actions have proven effective in improving the mechanical properties and heat-induced distortion of various metals and welding process. However, from the literature study, the pinpoint study in-cooling method used in a 3mm thick SS316L plate welded using Gas Tungsten Arc Welding (GTAW) has yet to be explored by any literature. This review is essential as the specific thickness of SS316L plate is used in vast industry applications, more over the maximum penetration of GTAW is approximately at 3 mm. This article additionally offers a comprehensive survey of the literature on cooling methods for solving problems in fusion and nonfusion welding involving various metals. The significant findings are then summarized to identify critical solutions to related issues and interesting potential areas that require further investigation to overcome or to reduce those challenges and problems. The recommendation is also made based on the summary of how the cooling method procedure will be applied to 3mm thick SS316L GTAW welds.